2016
DOI: 10.5897/ajb2015.15062
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular genetic diversity of Syrian indigenous goat populations

Abstract: Domestic goats in Syria may provide an interesting source of genetic variability due to its proximity to the centers of domestication. This study aimed to assess the morphological variation, genetic diversity and population substructure of the Syrian goat populations. Commonly, three goat genotypes are distinguished in Syria, namely Jabali or mountain goat, Baladi or local goat and Shami or Damascus (a well-known dairy goat). A pre-tested semi-structured questionnaire was used in recording both qualitative (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
2
4
1
Order By: Relevance
“…The low F IS values obtained in our study were contrasting with those found by other authors in goat populations [24,[26][27][28].…”
Section: Populationscontrasting
confidence: 99%
“…The low F IS values obtained in our study were contrasting with those found by other authors in goat populations [24,[26][27][28].…”
Section: Populationscontrasting
confidence: 99%
“…The presence of horns in animals is considered as an advantage for the drainage of blood through the cavernous sinus as a control mechanism for thermal homeostasis (Robertshaw, 2006). Horn orientation was mostly backward consistent with the results found for Syrian and Jordanian Baladi goats (Alrousan, 2009;Hassen et al, 2016). Straight nose was more common among does compared to bucks (half of does and one-fourth of bucks) while convex nose was more common among bucks than does.…”
Section: Discussionsupporting
confidence: 86%
“…About two-thirds of Baladi goats in the West Bank were horned similar to the results reported for Jordanian Baladi goats where 60% were horned (Alrousan, 2009). In contrast, 62.1% of Syrian Baladi goats were hornless (Hassen et al, 2016). All Cuban Creole goats and most Ethiopian indigenous goats (about 95%) had horns (Chacón et al, 2011;Hassen, Baum, Rischkowsky, & Tibbo, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations